2014
DOI: 10.1007/s00203-013-0951-1
|View full text |Cite
|
Sign up to set email alerts
|

Paludibacter jiangxiensis sp. nov., a strictly anaerobic, propionate-producing bacterium isolated from rice paddy field

Abstract: A mesophilic, obligately anaerobic, propionate-producing fermentative bacterium, designated strain NM7(T), was isolated from rural rice paddy field. Cells of strain NM7(T) are Gram-negative, non-motile, non-spore-forming, short rods, and negative for catalase. The strain grew optimally at 37 °C (the range for growth 15-40 °C) and pH 7.0 (pH 5.0-7.5). The strain could grow fermentatively on various sugars, including arabinose, xylose, fructose, galactose, glucose, mannose, cellobiose, lactose, maltose, sucrose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…Bacteroides (belonging to the class Bacteroidia ) took up the largest proportion of co-digesting tests, especially in S (23%) and HS (34%), and it was identified as one of the most dominant heterotrophic organisms in anaerobic wastewater treatment sludge and was capable of converting proteins and carbohydrates to HPr and HAc as its primary products in anaerobic sludge fermentation [41]. As one of class Bacteroidia , Paludibacter reached the highest abundance in S (4%), which was commonly considered to be a strictly anaerobic, HPr—producing bacterium [42]. Mangroviflexu (belonging to class Marinilabiaceae ), which was also mainly detected in S (7%), was an obligately anaerobic mesophilic microorganisms and be able to ferment various substrates with the production of HPr, HAc, and succinate [43].…”
Section: Resultsmentioning
confidence: 99%
“…Bacteroides (belonging to the class Bacteroidia ) took up the largest proportion of co-digesting tests, especially in S (23%) and HS (34%), and it was identified as one of the most dominant heterotrophic organisms in anaerobic wastewater treatment sludge and was capable of converting proteins and carbohydrates to HPr and HAc as its primary products in anaerobic sludge fermentation [41]. As one of class Bacteroidia , Paludibacter reached the highest abundance in S (4%), which was commonly considered to be a strictly anaerobic, HPr—producing bacterium [42]. Mangroviflexu (belonging to class Marinilabiaceae ), which was also mainly detected in S (7%), was an obligately anaerobic mesophilic microorganisms and be able to ferment various substrates with the production of HPr, HAc, and succinate [43].…”
Section: Resultsmentioning
confidence: 99%
“…An interesting case presents the detection of Paludibacter ( Bacteroidetes ). With only two species described, both isolated from paddy rice fields, not much is known about their ecology [21, 31]. None of the described species displayed psychrophilic growth characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Paludibacter jiangxiensis is another bacterium that utilizes sugars to produce propionate as the major product. However, compared with P. propionicigenes, it was found that yeast extract was not required for the growth of the bacterium [72]. Propionibacteria selectively produce propionic acid from organic matter and make up 1.4% of the ruminal microflora [73].…”
Section: Microbes Used For Propionic Acid Productionmentioning
confidence: 99%